The phenotype of Sotos syndrome in adulthood: A review of 44 individuals. Issue 4 (3rd September 2019) - Foster, Alison; Zachariou, Anna; Loveday, Chey; Ashraf, Tazeen; Blair, Edward; Clayton‐Smith, Jill; Dorkins, Huw; Fryer, Alan; Gener, Blanca; Goudie, David; Henderson, Alex; Irving, Melita; et al.
Abstract: Sotos syndrome is an overgrowth‐intellectual disability (OGID) syndrome caused by NSD1 pathogenic variants and characterized by a distinctive facial appearance, an intellectual disability, tall stature and/or macrocephaly. Other associated clinical features include scoliosis, seizures, renal anomalies, and cardiac anomalies. However, many of the published Sotos syndrome clinical descriptions are based on studies of children; the phenotype in adults with Sotos syndrome is not yet well described. Given that it is now 17 years since disruption of NSD1 was shown to cause Sotos syndrome, many of the children first reported are now adults. It is therefore timely to investigate the phenotype of 44 adults with Sotos syndrome and NSD1 pathogenic variants. We have shown that adults with Sotos syndrome display a wide spectrum of intellectual ability with functioning ranging from fully independent to fully dependent. Reproductive rates are low. In our cohort, median height in adult women is +1.9 SD and men +0.5 SD . There is a distinctive facial appearance in adults with a tall, square, prominent chin. Reassuringly, adults with Sotos syndrome are generally healthy with few new medical issues; however, lymphedema, poor dentition, hearing loss, contractures and tremor have developed in a small number of individuals.